Transition Metal Oxides and Li2CO3 as Precursors for the Synthesis of Ni-Rich Single-Crystalline NCM for Sustainable Lithium-Ion Battery Production. Issue 7 (1st July 2022) - Ruess, Raffael; Ulherr, Mark A.; Trevisanello, Enrico; Schröder, Steffen; Henss, Anja; Janek, Jürgen
Abstract : Single-crystalline Ni-rich LiNi1- x - y Co x Mn y O2 (SC-NCM) cathode active materials promise to increase the lifetime of high energy Li-ion batteries. SC-NCM consist of large primary particles that offer low surface area, limiting detrimental chemical reactions while exhibiting high morphological stability. A typical SC-NCM synthesis starts from the same Ni1- x - y Co x Mn y (OH)2 and LiOH∙H2 O precursors commonly used for conventional spherical poly-crystalline NCM (PC-NCM), but requires higher temperatures and additional post-processing. Consequently, the cost and environmental impact of the production of Ni-rich SC-NCM is higher compared to the production of PC-NCM. In this study, we demonstrate a synthesis of SC-NCM that does not require the same highly engineered precursors as used for PC-NCM. We propose a more energy-efficient and cost-effective route that involves simple blending of NiO, MnO, Co3 O4 and Li2 CO3 which yields single-crystalline LiNi0.83 Co0.11 Mn0.06 O2 with 2–3 μ m particle size and good structural quality. It is shown by in situ XRD during synthesis that—while the reaction suffers from slow kinetics—the elevated temperature and longer reaction time, which are in any case required for the crystal growth, are sufficient to also complete the reaction. Furthermore, it is shown that this material is structurally and electrochemically equivalent to the material commonly synthesized from hydroxide-based precursors.